Understanding psilocybin mushrooms and aiding in setting standards for a burgeoning industry in Jamaica - Rupika Delgoda; Kimberley Foster; Isaac Morrison; Marshall Tyler; William Irvine; Lavonne Wilson; Babumon M. Thankappan; Shemar Daniel (Phytochemistry Letters, 2025)

Retraction Note: Financial development and environmental sustainability in West Africa: evidence from heterogeneous and cross-sectionally correlated models - Mohammed Musah; Michael Owusu-Akomeah; Joseph Dery Nyeadi; Morrison Alfred; Isaac Adjei Mensah (Environmental Science and Pollution Research, 2024)

Retraction Note: Does energy consumption, economic growth, urbanization, and population growth influence carbon emissions in the BRICS? Evidence from panel models robust to cross-sectional dependence and slope heterogeneity - Hao Chen; Evelyn Agba Tackie; Isaac Ahakwa; Mohammed Musah; Andrews Salakpi; Morrison Alfred; Samuel Atingabili (Environmental Science and Pollution Research, 2024)

Retraction Note: Green investments, financial development, and environmental quality in Ghana: evidence from the novel dynamic ARDL simulations approach - Mohammed Musah; Michael Owusu-Akomeah; Emmanuel Attah Kumah; Isaac Adjei Mensah; Joseph Dery Nyeadi; Muntasir Murshed; Morrison Alfred (Environmental Science and Pollution Research, 2024)

The effect of casing and gypsum on the yield and psychoactive tryptamine content of Psilocybe cubensis (Earle) Singer - Kimberley Foster; Isaac Morrison; Marshall Tyler; Rupika Delgoda (Fungal Biology, 2024)

RETRACTED ARTICLE: Does energy consumption, economic growth, urbanization, and population growth influence carbon emissions in the BRICS? Evidence from panel models robust to cross-sectional dependence and slope heterogeneity - Hao Chen; Evelyn Agba Tackie; Isaac Ahakwa; Mohammed Musah; Andrews Salakpi; Morrison Alfred; Samuel Atingabili (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Green investments, financial development, and environmental quality in Ghana: evidence from the novel dynamic ARDL simulations approach - Mohammed Musah; Michael Owusu-Akomeah; Emmanuel Attah Kumah; Isaac Adjei Mensah; Joseph Dery Nyeadi; Muntasir Murshed; Morrison Alfred (Environmental Science and Pollution Research, 2022)

Reinvestigating the pollution haven hypothesis: the nexus between foreign direct investments and environmental quality in G-20 countries - Mohammed Musah; Isaac Adjei Mensah; Morrison Alfred; Haider Mahmood; Muntasir Murshed; Akoto Yaw Omari-Sasu; Frank Boateng; Joseph Dery Nyeadi; Cephas Paa Kwesi Coffie (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Financial development and environmental sustainability in West Africa: evidence from heterogeneous and cross-sectionally correlated models - Mohammed Musah; Michael Owusu-Akomeah; Joseph Dery Nyeadi; Morrison Alfred; Isaac Adjei Mensah (Environmental Science and Pollution Research, 2022)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Comparison of low-carbon pathways for California - Geoffrey M. Morrison; Sonia Yeh; Anthony R. Eggert; Christopher Yang; James H. Nelson; Jeffery B. Greenblatt; Raphael Isaac; Mark Z. Jacobson; Josiah Johnston; Daniel M. Kammen; Ana Mileva; Jack Moore; et al. (Climatic Change, 2015)

Conservation and Management of the Endangered Fiji Sago Palm, Metroxylon vitiense, in Fiji - Clare Morrison; Isaac Rounds; Dick Watling (Environmental Management, 2012)